Analysis of Adobe Block Manufacturing Techniques - Rojas-Molina, María (2023)
Historically, adobe blocks have been one of the most widely used materials in Ecuador's vernacular architecture due to their low cost and properties. However, in the last decades, its use has decreased as well as the manufacturing expertise. This article focuses on analyzing the adobe manufacturing process in the province of Cotopaxi. We propose a three-stage methodology: 1) documentary bibliographic stage of adobe manufacture and regional regulations. 2) observation stage in local adobe factories identifying the processes and raw material; 3) analysis stage of adobe raw material and experimentation of the material. The documented information facilitates the understanding of adobe manufacturing processes, achieving a reference repository that contributes to sustainable development by using low impact construction materials that are easy to incorporate into architecture.